Tribological Behaviors of Molybdic Acid–Modified Phenolic/Polyfluo Wax Composite Coating. Issue 3 (3rd May 2016) - Yang, Ming-Ming; Zhang, Zhao-Zhu; Zhu, Xiao-Tao; Men, Xue-Hu; Ren, Gui-Na; Liu, Wei-Min
ABSTRACT: Phenolic resin (PF) and molybdic acid–modified phenolic (Mo-PF) have been synthesized and developed and combined with polyfluo wax (PFW) to fabricate PF-PFW and Mo-PF-PFW composite coatings. The effects of applied load and sliding speed on the tribological properties of the phenolic composite coating were evaluated using a block-on-ring wear tester. Compared to the PF composite coating, the Mo-PF displayed a lower friction coefficient and a higher wear life under all tested conditions. Scanning electron microscope (SEM) investigation showed that the Mo-PF composite coating had a smooth worn surface after the friction test, and a continuous and uniform transfer film was formed on the surface of the counterpart ring. The improved tribological properties of Mo-PF composite coating resulted from its enhanced thermal properties.